Interleukin-17A Inhibitor–induced Crohn's Disease/Behçet's Disease–like Lesions. Issue 6 (June 2017) - Shiga, Hisashi; Fukuda, Sho; Iijima, Katsunori
Abstract : Article first published online 2 May 2017.